Beat classification for use in arrhythmia analysis - REILLY, RICHARD (IEEE, 2000)
An important step in the classification of arrhythmias is beat classification. The aim of this work is to classify the beats in the MIT-BIH Arrhythmia database and to investigate pertinent features for beat classification. A comparison is made of the classification performance using features obtained after three different processing tasks on the electrocardiogram. QRS detection, QRS onset/offset detection and P wave onset detection. Linear discriminants and quadratic discriminants were employed to model the classifier. The best classification performance of 82% was achieved by employing the QRS width as an input feature to the linear discriminant classifier
PUBLISHED
Keywords: arrhythmias